On the Solvability of Second-Order Impulsive Differential Equations with Antiperiodic Boundary Value Conditions. (26th November 2008) - Xing, Yepeng; Romanovski, Valery
Abstract : We prove existence results for second-order impulsive differential equations with antiperiodic boundary value conditions in the presence of classical fixed point theorems. We also obtain the expression of Green's function of related linear operator in the space of piecewise continuous functions.